Pengaruh Return On Assets (ROA) Dan Debt To Equity Rasio (DER) Terhadap Return Saham (Studi Kasus Perusahaan Subsektor Otomotif & Komponen Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2020) - Ilham Wijaya; Dian Hakip Nurdiansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of Return on Assets (ROA) and Debt to Equity Ratio (DER) on Stock Return. Sampling using purposive sampling, from 11 samples of companies. This study uses secondary data from the financial statements of the Automotive and Component Subsector Companies listed on the Indonesia Stock Exchange 2014-2020. Multiple linear regression analysis was tested using SPSS 22 with normality test, multicollinearity test, heteroscedasticity test, autocorrelation, t-test, f-test, and coefficient of determination. In the test, ROA partially affects stock returns and DER has no effect on stock returns and simultaneously ROA and DER affect stock returns. Keywords: ROA. DER, Stock Return